The contribution of corporate ventures to radical innovation - Dirk Czarnitzki; Johannes M. H. Dick; Katrin Hussinger (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2010)
Established firms often face significant obstacles to innovation. As a solution, it has been suggested to form corporate ventures. Based on a sample of corporate and independent ventures in German manufacturing, we show that corporate ventures are more innovative than the control group, i.e. the independent ventures. In particular, corporate ventures are more successful at developing radical innovations. This effect, however, decreases with the ventures' degree of ownership concentration. We conclude that corporate ventures with a high ownership concentration are more likely to be controlled and monitored by their corporate sponsors, resulting in less favorable conditions for radical innovation.
Keywords: L26; M13; O31; O32; 330; corporate entrepreneurship; start-ups; radical innovation; Unternehmensgründung; Betriebsaufspaltung; Innovation; Risikokapital; Deutschland